The challenges of imaging based computational fluid dynamics - Cheng, Gary; Ito, Yasushi; Anayiotos, Andreas (My University, 2004)
Image based Computational Fluid Dynamics (CFD) simulation of the cardiovascular system is increasingly becoming important and its application in everyday medical practice can already be envisaged. The goal of this workshop is to address all the factors involved in the development of a computational framework/software for modelling and analyses of the cardiovascular system and provide examples. The development of such framework, requires integration, management and interpretation of data from several technology areas such as a) feature detection and extraction of arterial geometry from imaging data, b) adaptive grid generation techniques for 3-D asymmetric geometries c) hemodynamic modelling, disparate length-scale model, and fluid-tissue interaction with high-performance computing, d) CFD data validation, e) feature extraction/detection and visualisation algorithms, f) graphical user interface to allow remote visualisation of post processed data. These computational tools are employed to study flow in specific problem sites in the vascular tree such as the carotid, femoral, coronary and abdominal arteries. Such studies provide understanding of the factors involved in the initialisation and evolution of arterial disease due to altered flow conditions (as a result of plaque formation) such as flow separation and reversal, and low and oscillatory wall shear stress. It is also used to study the effect of various clinical procedures such as the implantation of stents, vascular grafts, vascular prostheses and artificial valve implants on local and global hemodynamics. This workshop will address a new emerging paradigm in clinical practice known as predictive medicine for effective surgical planning and post surgical rehabilitation. The workshop will also address the difficulties in the implementation of some of the technology areas in this application with examples of carotid, femoral, and abdominal artery simulations.
Keywords: Algorithms; Blood--Rheology; Computer interfaces